Analisis Pesan Dakwah Yang Terkandung Dalam Sinetron Pera Pencari Tuhan Jilid 14 - Ariefuddin Qhamarullah; Asep Gunawan; Noneng Siti Rosidah (Universitas Pahlawan Tuanku Tambusai, 2023)
Sinetron (Indonesian Soap opera) are a medium that functions to convey messages in audio-visual form. As an information medium, sinetron (Indonesian soap operas) can be said to be the most effective medium in conveying messages containing da'wah to the public. One of the Sinetron (Indonesian Soap opera) that can convey messages containing da'wah is the sinetron (Indonesian soap opera)